UV-Light-Induced Dehydrogenative N-Acylation of Amines with 2-Nitrobenzaldehydes To Give 2-Aminobenzamides - Zeng, Dishu; Yang, Tianbao; Tang, Niu; Deng, Wei; Xiang, Jiannan; Yin, Shuang-Feng; Kambe, Nobuaki; Qiu, Renhua (Synthesis, 2022)
A simple, mild, green, and efficient method for the synthesis of 2-aminobenzamides is highly desirable. Herein, we report the development of an efficient, one-pot strategy starting from 2-aminobenzaldehydes and amines with acetic acid in ethyl acetate/acetone using irradiation with UV light for the synthesis of 2-aminobenzamides in high yields; 32 examples proceeded successfully by this photo-induced protocol in up to 92% yield. The reaction was also readily achieved on a gram scale. The utility of the 2-aminobenzamide building block in organic synthesis was shown by their use in the preparation of quinazolinone derivatives. The method was applied to amino acid derivatives as the amine component, which smoothly gave N-(2-aminobenzoyl)acetate derivatives at room temperature. Finally, a plausible mechanism is proposed.
Keywords: UV-light-induced; amidation; nitro reduction; 2-aminobenzamide; 2-aminobenzaldehyde; quinazolinone